Fokus: technika i jej zastosowanie w badaniach edukacyjnych - Banaszak, Sławomir (Studia Edukacyjne, 2017)
A Focus group interview (FGI), the focused group, focus groups or just focus are the definitionsof data collection techniques which, after several decades of development, have become an important part of research plans in social sciences. Placing the focus on communication techniques leads us to combine analyses consisting of interview and observation. It also raises the question whether the focus, which by definitioncombines and directly expresses the strengths and weaknesses of communication techniques and the strengths and weaknesses of observation techniques, allows achieving some kind of methodological synergy. In addition, the essence of measurement in science and – more closely – in social sciences seems to be an important context for the empirical functioning of the focus and for researchers preferring this technique of data collection.